ICT, EFL teacher development and the reform of college English in China: an implementation study - Hu, Zhiwen (2009)
The purpose of this study was to investigate ICT-related EFL teacher development in the context of Chinese national College English reform. Four aims were established. First, to examine the current situation in a specific institution from the perspectives of: 1) teachers' attitudes towards ICT use in the context of College English reform; 2) the integration of ICT in English classes; 3) provision of ICT support within current continuing professional development (CPD) programmes for EFL teachers. Second, to assess the suitability of the CPD policies and practices for EFL teachers as a way of supporting the national College English reform. Third, to identify key issues affecting the effective provision of CPO in relation to ICT for EFL teachers. Fourth, to suggest possible solutions to problems identified and directions for future research. The study employed a case study involving quantitative and qualitative methods in order to give an in-depth account of the process of implementation of the reform at particular point in time. The findings indicated that initially the majority of teachers had held positive attitudes towards ICT use in English teaching and the national reform, but their enthusiasm was waning in the light of inadequate support and training. The national reform had, however, stimulated the improvement of ICT competence of both teachers and students. At the same time, it had challenged EFL teachers to adapt to new teaching materials, student-centred classroom teaching and how to guide students in their autonomous learning. In terms of ICT-related CPD policies and practices, there existed a gap between the current policies in the provision of CPD and demand for this. Recommendations are made for future research and for improvements in policy and practice of ICT-related CPD for EFL teachers in China.